Activity measurements of methanogenic Archaea isolated from Siberian Permafrost under simulated Mars analog conditions - Malaszkiewicz, Janosch; Wagner, Dirk (2010)
The environmental conditions of early Mars and early Earth are assumed to have been most similar. The oldest proofs of life on Earth, which can be found as microfossils in Archaean rocks, date back to this time of about 3.8 Ga ago. Regarding this one can presume that life might have evolved on Mars, too. Martian life must have adapted to the drastic change of conditions on the planet or become extinct. Plausible forms of still existing prokaryotic life on Mars are lithoautothrophic subsurface ecosystems. Comparable environments exist in the permafrost regions on Earth.On Mars frozen water in form of surface glaciers and subsurface ground ice layers but also water in a liquid state - which is one of the most important factors for the existence of life - could be observed by NASA and ESA missions. The detection of methane on Mars by Mars Express lead to the conclusion that it must be of a recent origin because of its rather short persistence time in the atmosphere of a few hundreds of years. Thinkable sources of the methane are active volcanism - that could not yet be observed on modern Mars - or biogenic production. The correlation between the presence of water vapour and methane on the Martian surface which occur both in higher concentrations in the same regions and time intervals are an indication of a biological source of the methane on Mars. Methanogenic archaea from terrestrial permafrost regions are therefore one of the most suitable candidates for possible existing life on Mars. They have evolved under early Earth conditions, grow lithoautotorphicly under strictly anaerobic surroundings, are able to tolerate low temperatures and have survived in the extreme environments of permafrost affected soils for several millions of years.This PhD project is associated to the Helmholtz-Alliance Planetary Evolution and Life and is focused on experiments with strains of methanogenic archaea that have been isolated from the active layer of permafrost on Samoylov Island in the Lena Delta, Siberia. Former experiments with ...